Association between bodyweight perception, nutritional status, and weight control practices: A cross-sectional analysis from the Chilean Health Survey 2016–2017 - Nazar, Gabriela; Alcover, Carlos-María; Lanuza, Fabián; Labraña, Ana María; Ramírez-Alarcón, Karina; Troncoso-Pantoja, Claudia; Leiva, Ana María; Celis-Morales, Carlos; Petermann-Rocha, Fanny (Frontiers in Psychology, 2022)
This research aimed to 1) examine the agreement between BMI-based nutritional status and perceived nutritional status overall and by socio-demographic factors, and 2) to state the association between the accuracy of weight perception and weight control practices in the Chilean adult population. A population-based cross-sectional study with 5,192 Chilean adult participants from the Chilean National Health Survey 2016-2017 was carried out. Agreement between BMI-based weight status and body weight perception for the total sample and across subgroups was determined using the kappa coefficient. The agreement between BMI-based and perceived nutritional status of the total sample was fair (kappa= 0.24). A higher rate of weight perception accuracy was identified in women, younger respondents, and participants with higher education, a higher income, and from urban areas than their counterparts. Respondents with overweight or obesity tend to underestimate their nutritional status. Actions to lose weight were higher in those who have the right perception of their overweight/obesity condition and those who overestimated their body weight, regardless of their nutritional status. In all groups, weight loss behaviors were more related to the perceived than the BMI-based nutritional status. The consequences of accurate perception of the nutritional status are discussed including its effects on body weight and mental health.